Vibration control of a Stirling engine with an electromagnetic active tuned mass damper. (June 2016) - Hassan, Ali; Torres-Perez, Angel; Kaczmarczyk, Stefan; Picton, Phil
Abstract: Active tuned mass damper (ATMD) systems have been used extensively to reduce vibrations in machines. The motivation of this study is attenuating the vibrations in a Free-Piston Stirling Engine/Linear Alternator (FPSE/LA) for a frequency band of 47–53 Hz using an electromagnetic ATMD that employs a linear Voice Coil Motor (VCM) for periodic excitation rejection. To the authors' knowledge, however several approaches to minimize vibrations in Stirling machines have been patented, the technique proposed in this research differs from other patented work by the simplicity of the proposed control law which aims to attenuate the engine vibrations at the fundamental operating frequency. The proposed control system features a zero-placement technique that utilizes both relative or absolute position and velocity feedback from the system response as well as a feedthrough measurement of the disturbance frequency that is used to determine the position gain online. The performance of the control system with the ATMD was evaluated both theoretically and experimentally. A test rig emulating the vibration behavior of the Stirling engine, featuring an electrodynamic shaker and an ATMD was developed and a model of the rig is presented and validated. A novel experimental procedure of identifying unknown stiffness and unknown dynamic mass of a spring–mass system is also presented. Similarly, another experimental procedure of determining the damping coefficient in the electromagnetic ATMD is shown. The implementation findings illustrate that the proposed active controller succeeds in broadening the attenuation band from 50±0.5 Hz to between 45 Hz and 55 Hz. Highlights: Active vibration control law is proposed and tested for a Stirling machine with an ATMD. Position and velocity feedback for disturbance rejection with gain scheduling. The control law was tested experimentally and a wider frequency bandwidth is achieved. The damping introduced ATMD was found to vary with frequency non-linearly. A novel experimental technique was followed to determine the damping in the ATMD.